Clinical Use of Cerebral Microdialysis in Patients with Aneurysmal Subarachnoid Hemorrhage—State of the Art - Helbok, Raimund; Kofler, Mario; Schiefecker, Alois Josef; Gaasch, Maxime; Rass, Verena; Pfausler, Bettina; Beer, Ronny; Schmutzhard, Erich (Frontiers in Neurology, 2017)
Objective: To review the published literature on the clinical application of cerebral microdialysis (CMD) in aneurysmal subarachnoid hemorrhage (SAH) patients and to summarize the evidence relating cerebral metabolism to pathophysiology, secondary brain injury, and outcome. Methods: Study Selection: Two reviewers identified all manuscripts reporting on the clinical use of cerebral microdialysis in aneurysmal SAH patients from MEDLINE. All identified studies were grouped according to their focus on the brain metabolic changes during the early and subacute phase after SAH, their association with mechanisms of secondary brain injury and outcome. Results: The review demonstrated: 1. Very limited literature is available in the very early phase before the aneurysm is secured. 2. Brain metabolic changes related to early and delayed secondary injury mechanisms may be used in addition to other neuromonitoring parameters in the critical care management of SAH patients. 3. CMD markers of ischemia may detect delayed cerebral ischemia early (up to 16 hours before onset), underlining the importance of trend analysis. 4. Various CMD-derived parameters may be associated with patient outcome at 3 to 12 months, including: CMD-lactate–to–pyruvate-ratio, CMD-glucose and CMD-glutamate. Conclusions: The clinical use of CMD is an emerging area in the literature on aneurysmal SAH. Larger prospective multi-center studies on interventions based on CMD findings need to be conducted.